1993
DOI: 10.1006/cbir.1993.1140
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effects of heparin on normal and transformed NIH/3T3 fibroblasts.

Abstract: We studied the effect of heparin on proliferation and signalling in normal NIH/3T3 fibroblasts, and in cells transformed by different oncogenes. Heparin inhibited the proliferation of normal as well as of v-sis and v-erbB transformed fibroblasts in the presence of serum, but failed to inhibit v-erbB-driven proliferation in serum-starved cultures; under these conditions, heparin inhibited by approximately 50% the proliferation of normal and v-sis- transformed cells. Heparin also inhibited PDGF-induced cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
3
11
0
Order By: Relevance
“…The expression level of tiGHR that we obtained for each studied tissue can be organized in decreased order of expression levels as: liver > muscle > brain > heart > gonads > intestine > stomach > spleen (Figure 6). The highest expression level of tiGHR I in liver is consistent with previous receptor binding studies [20]. Besides, it is in agreement with previous conventional RT-PCR studies [4,6] and with real-time PCR studies [24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The expression level of tiGHR that we obtained for each studied tissue can be organized in decreased order of expression levels as: liver > muscle > brain > heart > gonads > intestine > stomach > spleen (Figure 6). The highest expression level of tiGHR I in liver is consistent with previous receptor binding studies [20]. Besides, it is in agreement with previous conventional RT-PCR studies [4,6] and with real-time PCR studies [24].…”
Section: Discussionsupporting
confidence: 92%
“…We have also been able to detect expression of this receptor in all studied tissues, which is consistent with the pleiotropic nature of growth hormone in fish [20-23]. The expression level of tiGHR that we obtained for each studied tissue can be organized in decreased order of expression levels as: liver > muscle > brain > heart > gonads > intestine > stomach > spleen (Figure 6).…”
Section: Discussionsupporting
confidence: 80%
“…The selectivity of effects was demonstrated by studying in parallel normal human embryonic kidney cells that, at variance with cancer cells, were protected by the compound. These results are consistent with our old observation that glycosaminoglycans exert opposite effects in normal and cancer cells (Cavari et al, 1993), thus being excellent candidates for a novel type of immunotherapy that is based on these macromolecules instead of proteins. In addition to these considerations regarding the glycosaminoglycan moiety of Rerum ® , it should be noticed that also the fatty acid (oleic acid) moiety of the compound shows selective anti-cancer properties.…”
Section: The Development Of a Novel Approach To Glycosaminoglycan-bassupporting
confidence: 92%
“…More specifically, we demonstrated that heparin inhibited proliferation and signaling induced by the PlateletDerived Growth Factor (PDGF) in cancer cells transformed by the oncogene sis that is the oncogene coding for PDGF. However, in normal, non-neoplastic, cells, heparin did not affect the signaling of the same growth factor PDGF as if the anti-oncogene effect of the glycosaminoglycan were selective for cancer cells (Cavari et al, 1993). These results were of utmost importance for the future molecular design of Rerum ® because they provided the first experimental evidence that we could selectively target cancer cells without interfering with normal cell functions, an effect, a sort of "Holy Grail", that has been sought after since the beginning of the fight by humans against cancer.…”
Section: An Alternative Approach To Immunotherapy; the Role Of Glycosmentioning
confidence: 87%
“…Heparin affects both dermal fibroblast proliferation [1][2][3][4][5] and collagen production. 2,[6][7][8] Several studies have also demonstrated decreased production of collagen by dermal fibroblasts exposed to heparin.…”
mentioning
confidence: 99%